Développement du média Smart Box pour améliorer les compétences de français des élèves de SMAN 21 Medan - Chafizah Nur'ain Harahap; Zulherman (Didacticofrancia Journal Didactique du FLE, 2026)
This study aims to develop “smart box” materials for learning French at the secondary level, and to determine the feasibility of the “smart box” materials developed. The research employs the research and development (R&D) method, using Robert Maribe Branch’s ADDIE model (2009). The research did not reach the stage of product effectiveness testing. The research stages began with information gathering and needs analysis through the distribution of questionnaires to students; design through the collection of learning materials and the manufacture of learning aids in accordance with the design; and validation of the intelligent toolbox with media and materials experts. The results of the validation test by media experts were 81.54%, and by material experts, 82%. Media validation results are included in the “very good” category. Material validation results are included in the “very good” category.